2019
DOI: 10.1080/16522354.2019.1630099
|View full text |Cite
|
Sign up to set email alerts
|

“They’re a little bit squeezed in the middle”: Strategic challenges for innovation in US Metropolitan newspaper organisations

Abstract: This paper focuses on media innovation among publishers of metropolitan newspapers in the United States, in cities such as San Diego, Boston, Miami, Philadelphia and Dallas. The situation for metropolitan newspapers is difficult, as they fall between national newspapers, which can aim for extending their reach both nationally and globally, and local newspapers, which have a smaller cost structure and can cater to a more limited, and often more engaged, audience community. Our paper demonstrates that there seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
21
0
2
Order By: Relevance
“…Overall, our findings support what previous research on media innovation has found: Innovation in regional and metropolitan legacy media newsrooms is still more about exploitative, incremental innovation and less about explorative, "outside the box", innovation (Krumsvik et al 2019;Malmelin and Nivari-Lindstr€ om 2017;Porcu 2017). The findings portray how change is notoriously hard to achieve in legacy media newsrooms (Villi et al 2020;Ekdale et al 2015;Ess 2014). However, our findings also point to a possible remedy: Building a strong PSCC could help media organizations in achieving a fertile environment for an innovative learning culture (ILC) that triggers and fosters much needed explorative innovation (Porcu 2017;Porcu, Hermans, and Broersma 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our findings support what previous research on media innovation has found: Innovation in regional and metropolitan legacy media newsrooms is still more about exploitative, incremental innovation and less about explorative, "outside the box", innovation (Krumsvik et al 2019;Malmelin and Nivari-Lindstr€ om 2017;Porcu 2017). The findings portray how change is notoriously hard to achieve in legacy media newsrooms (Villi et al 2020;Ekdale et al 2015;Ess 2014). However, our findings also point to a possible remedy: Building a strong PSCC could help media organizations in achieving a fertile environment for an innovative learning culture (ILC) that triggers and fosters much needed explorative innovation (Porcu 2017;Porcu, Hermans, and Broersma 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The corporation owns regional and local newspapers in various parts of Finland to which the teams cater their content to. Considering that both teams are focused on content production rather than research and development, they are a typical example of journalistic teams found in regional/metropolitan newspapers and as such, they illustrate the challenges presented to metropolitan newspapers by their position between national and more local news outlets (see Villi et al 2020). We wanted to examine creative work and innovation in journalistic teams in regional newspapers with limited resources rather than focusing on R&D teams in well-funded, quite atypical, media organizations (such as The New York Times or The Washington Post would be in the US context).…”
Section: Organizational Communication Meets Journalism: Idea Sharing mentioning
confidence: 99%
“…Social media platforms, and Facebook in particular, have recently become the most frequent source of news for people in this region (Olsen, Solvoll, & Gran, 2018), but there are signs of a general trend away from dependence on platforms (Lindén, 2020). Legacy media is struggling with its business model, but the larger commercial media companies, such as Bonnier, Schibsted, Sanoma and Amedia, are successfully transitioning from mixed revenues-advertisement and subscriptions-to paid digital content (Villi et al, 2019).…”
Section: Background and Motivating Questionsmentioning
confidence: 99%
“…In comparison to workers in other industries, media workers have been among the first to have to adjust to digitalization in working life, with its positive and negative effects (Malmelin and Villi, 2017), and the more extensive job descriptions with their demands of multi-competences (Bakker, 2014;Deuze and Witschge, 2018). Moreover, due to digital disruption in the production and consumption of media products, media organizations have had to increasingly dismiss workers, which has led to work intensification among those who have kept their jobs (Villi et al, 2020).…”
Section: Ijds and Cognitive Stress Symptoms In The Context Of Media Workmentioning
confidence: 99%